Association between the COVID-19 outbreak and opioid prescribing by U.S. dentists - Zhang, Jason; Nalliah, Romesh P.; Waljee, Jennifer F.; Brummett, Chad M.; Chua, Kao-Ping (PLOS ONE, 2023)
Background U.S. data on opioid prescribing by dentists are limited to 2019. More recent data are needed to understand the effect of the COVID-19 outbreak on dental opioid prescribing, characterize current practices, and determine if dental opioid stewardship initiatives are still warranted. Objective To evaluate the association between the COVID-19 outbreak and the rate of opioid prescribing by U.S. dentists Methods During February—April 2023, the authors conducted a cross-sectional analysis of the IQVIA Longitudinal Prescription Database, which reports 92% of prescriptions dispensed in U.S. retail pharmacies. The authors calculated the monthly dental opioid dispensing rate, defined as the monthly number of dispensed opioid prescriptions from dentists per 100,000 U.S. individuals, during January 2016-February 2020 and June 2020-December 2022. To prevent distortions in trends, data from March–May 2020, when dental opioid dispensing declined sharply, were excluded. Using linear segmented regression models, the authors assessed for level and slope changes in the dental opioid dispensing rate during June 2020. Results Analyses included 81,189,605 dental opioid prescriptions. The annual number of prescriptions declined from 16,105,634 in 2016 to 8,910,437 in 2022 (-44.7%). During January 2016-February 2020, the dental opioid dispensing rate declined -3.9 (95% CI: -4.3, -3.6) per month. In June 2020, this rate abruptly increased by 31.4 (95% CI: 19.3, 43.5) and the monthly decline in the dental opioid dispensing rate slowed to -2.1 (95% CI: -2.6, -1.6) per month. As a result, 6.1 million more dental opioid prescriptions were dispensed during June 2020-December 2022 than would be predicted had trends during January 2016-February 2020 continued. Discussion U.S. dental opioid prescribing is declining, but the rate of this decline slowed after the COVID-19 outbreak. Findings highlight the continued importance of dental opioid stewardship initiatives.